DIGITAL PRACTICES TO ENHANCE INTANGIBLE CULTURAL HERITAGE - E. C. Giovannini; M. Lo Turco; A. Tomalini (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2021)
The term “cultural heritage” has been enriched with multiple contents in the last decades, partly thanks to the protection instruments developed by UNESCO. Despite the past, the cultural heritage is not limited to monuments and collections of objects. The term nowadays includes tangible and intangible cultural heritage (ICH). ICH includes traditions or living expressions inherited from our ancestors and passed on to our descendants, such as oral traditions, performing arts, social practices, rituals, festive events, knowledge and practices concerning nature and the universe or the knowledge and skills to produce traditional crafts. Within this context, the Museum of “Passione di Sordevolo” preserves and spreads the cultural and social value of the largest representation of popular Christian theatre in Italy, called “La Passione di Sordevolo”. The paper presents the results of the research of the reconstructive modelling and visual storytelling project called "Digital historical scenic design". The project explores the use of digital technologies to create new content compatible with the Museum’s mission: dissemination, communication and valorization of the documentary heritage (photographs, sketches, drawings) and the systematic collection of the oral tradition of this theatrical tradition.